What is sum of 67³ and 89³
Answers
Answered by
1
Answer:
1,005,732
Step-by-step explanation:
plz mark me as BRAINLIST
Answered by
3
Hey dear♥️
COMMON PROCESS :
67³ + 89³
= (67×67×67) + (89×89×89)
= 300763 + 704969
= 1005732
______________________________
USING IDENTITY :
This equation is in the form of a³ + b³
so using identity,
a³ + b³ = (a + b) (a² - ab + b²)
67³ + 89³ = (67 + 89) [67² - (67×89) + 89²]
RHS = (67 + 89) [67² - (67×89) + 89²]
= 156 [ 4489 - 5963 + 7921]
= 156 × 6447
= 1005732
hence, 67³ + 89³ = 1005732
Thank u :)
Similar questions
Environmental Sciences,
5 months ago
Math,
5 months ago
Business Studies,
5 months ago
Social Sciences,
11 months ago
Math,
11 months ago
Environmental Sciences,
1 year ago
Math,
1 year ago